2020
DOI: 10.7150/jca.37117
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cancer stemness provides luminal a breast cancer cells with HER2 positive-like features

Abstract: Breast cancers can be classified into luminal A, luminal B, HER2 positive and triple-negative subtypes, each with a distinct therapeutic response. Tumor stemness drives cancer malignancy that challenges cancer control. Understanding the revolutionary relationships driven by tumor stemness among breast cancer subtypes is fundamental to identifying feasible therapeutic modalities for each breast cancer subtype. Utilizing the endogenous tRNA-processing system, we established a multiplexing CRISPR/dCas9 system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In addition, CSCs also have DNA repair and antiapoptotic effects 23 , which are responsible for resistance to treatment. What’s more, different BC molecular subtypes, such as TNBC cells and HER-2 positive cells, has the similar stemness, but they are tow unique diseases that require different treatment strategies 24 . In BCSCs of different molecular subtypes, the expression and regulation of HER-2 are both different, so therapeutic repercussion and prognosis of patients will be different 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CSCs also have DNA repair and antiapoptotic effects 23 , which are responsible for resistance to treatment. What’s more, different BC molecular subtypes, such as TNBC cells and HER-2 positive cells, has the similar stemness, but they are tow unique diseases that require different treatment strategies 24 . In BCSCs of different molecular subtypes, the expression and regulation of HER-2 are both different, so therapeutic repercussion and prognosis of patients will be different 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Low PinX1 expression is associated the malignant behavior of these cells. Mei et al ( 27 ) successfully designed an efficient multiplexed CRISPR/dCas9 system using CRISPR/Cas9 technology, and applied it to study the phylogenetic relationship between breast cancer subtypes driven by cancer stems, and clarified that Differentiating the treatment strategies of triple-negative breast cancer and HER-2 positive breast cancer. The CRISPR/Cas9 system has provided a plethora of ideal methods to improve cell and animal models for studying the functions of genes and biological progresses; therefore, it has greatly promoted the study of various diseases in vitro and in vivo ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mei et al (2020) have demonstrated the evolutionary relationships in breast cancer subtypes by developing a multiplexing CRISPR/dCas9 system. 86 Various applications of CRISPR-Cas system in cancer treatment have been shown in Figure 4 .
Figure 4 Therapeutic applications of CRISPR-Cas system in cancer.
…”
Section: Emerging Therapeutic Applications Of Crispr Technologymentioning
confidence: 99%
“… Breast cancer Breast cancer cells OCT4 , KLF , MYC , SOX2 Study the phylogenetic relationships among breast cancer subtypes as stratified by cancer stemness MCF7, SKBR3 and MDAMB231 Genome editing by overexpressing of OCT4 , KLF , MYC , SOX2 85 6. Colon organoids Human colonic stem cells mismatch repair gene MLH1 Explore the origin of cancer-associated mutational signatures MLH1 KO and NTHL1 KO Delete key DNA repair genes followed by delayed subcloning and whole-genome sequencing 86 …”
Section: Emerging Therapeutic Applications Of Crispr Technologymentioning
confidence: 99%